Small choroidal melanoma and pseudomelanomas: methods of differential diagnostics (literature review). Part 2 - E. B. Myakoshina (Российский офтальмологический журнал)
The first part of the literature review described the ophthalmoscopic picture of the small choroidal melanoma and pseudomelanomas [ROJ, 2019; 12 (4): 99–108]. This is the second part of the review, which describes the features characteristic of small uveal melanoma and pseudomelanomas, revealed by fluorescence angiography and autofluorescence. Typical properties of fluorescence and autofluorescence are presented for every disease of the eye fundus studied: small choroidal melanoma, choroidal nevus, circumscribed choroidal hemangioma, melanocytoma, choroidal metastatic carcinoma, congenital hypertrophy of the retinal pigment epithelium, late-stage age-related macular degeneration, focal retinochoroiditis of the posterior pole, organized subretinal hemorrhage, retinal hemangioma. The attention was focused on the similarity of angiographic and autofluorescence symptoms of the diseases under study. The need for new differential diagnostic criteria was emphasized.